Upaya Meningkatkan Fisik dan Kelincahan Siswa dengan Metode Ilinois Run pada Ekstrakurikuler Futsal - Olivia Dwi Cahyani; Aris Prasetyo; Heru Hermawan (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Futsal sport is one of the activities that require good techniques, tactics and physical conditions in futsal extracurricular activities requires good physical condition in order to have an effect on the players. This study aims to find out the physical condition of futsal extracurricular participants at SMPN 2 Padangan. The research technique used in this study is a survey technique in the form of descriptive research in the form of quantitative data collection, testing and measurement using the ilinois agility runs method on 25 students who participated in extracurricular futsal with a research duration of one week. The results of this study classified futsal participants into the categories of "good" speed, "good" mobility, and "good" cardiorespiratory endurance. In the formula for categorizing futsal extracurricular participants, the category is sufficient so that it can be concluded that futsal extracurricular participants have sufficient category physical conditions. Based on the results of calculations and data analysis, it can be concluded that there have been changes in students due to the influence of the direct class learning model on Ilinois and skill learning.